Climate and environmental Crop Risk Index (CRI) - Lenaerts, Bert; Badayos, Gerdino (2025)
The objective of this project is to develop a crop production risk index that enables the quantification of expected yield changes in the future, facilitating benefit modelling. The crop risk index is based on a hazard-risk framework and utilises spatial data on climate and environmental factors, combined with expert estimates (see Table 1). This simplified approach aims to address limitations encountered in traditional crop modelling, such as inadequate coverage, missing salinity modules, and constraints related to computing capacity, ultimately enhancing the scalability of yield predictions.